Female Leader As Sui Generis Reflected In Iron Lady Movie (2012) Directed By Phyllida Lloyd: A Feminist Approach - Utami, Utami; , Dr. Phil. Dewi Candraningrum, S.Pd., M.Ed; , Titis Setiabudi, SS, M.hum (2013)
The object of the study is a movie Iron Lady directed by Phyllida Lloyd. The study is to reveal how female leader as sui generisis reflected in Iron Lady directed by Phyllida Lloydpublished in 2012. The objective of the study is to analyze the structural elements in the movie and to analize female leader as sui generis as leader of the movie based on feminist approach. The researcher employs the descriptive qualitative research as a type of the research. The data sources are divided into two, namely primary data source and secondary data source. The primary data source is the events of the movie and script of Iron Lady and the secondary data source is biography of Margaret Thatcher as major character. The method of collecting data is documentation. The technique of analyzing data is descriptive. The result of the study is as follows: First, based on the structural analysis, Phyllida Lloyd delivers a moral message that a woman as leader is a unique person on her own kind. Women have equal opportunity to achieve their goals of life in all aspects. Second, based on the feminist analysis, Phyllida Lloyd reflects that women have to strive equal opportunity to be a leader and equal treatment in society and politic. Women as leader are extraordinary.